Lifelong activism and women's entrepreneurship: how a social movement organization improves conditions for self-employed women in India. Issue 5 (12th June 2020) - Colovic, Ana; Mehrotra, Sonia
Abstract : Purpose: The purpose of this paper is to investigate how a local trade union improves living conditions for women entrepreneurs in India and how its activities have evolved over time. Design/methodology/approach: The authors conducted a longitudinal case study of the self-employed women's association (SEWA) in India. Founded in 1972, this organization fosters and supports women's entrepreneurship. The approach of this study combines qualitative face-to-face interviews and secondary data analysis. Findings: The findings highlight the fact that SEWA, which combines the features of a trade union and a social movement, improves women's conditions in several different ways. The study shows that the organization's main role has evolved from creating a community to expanding it and finally to becoming an agent of societal change. Originality/value: The study contributes to the literature by analyzing how locally grown organizations fight social exclusion and improve the conditions of deprived groups in emerging economies.